Penerapan model pembelajaran inquiry training dan model pembelajaran kooperatif tipe group investigation berbantuan laboratorium mini pada hasil belajar siswa kimia di SMA - I Kadek Cenik; Sonny Lumingkewas; Meiske Naomi Mamuaja (Chemistry Department, Universitas Negeri Manado, 2019)
This study aims to determine whether there are differences in the average student learning outcomes taught with the Inquiry Training learning model and the Group Investigation learning model on electrolyte and non-electrolyte solution material. This research was conducted at SWADHARMA WERDHI AGUNG High School in second semester of 2017/2018. The research method used is the experimental method. Sampling is done by random sampling technique. The sample in this study was class XA students as experimental class I and class XB as experimental class II. Each sample amounted to 20 respondents, and the total number of respondents was 40. Data collection techniques were pretest and posstest and the instruments used to measure learning outcomes were multiple choice tests. Analysis of the posttest data of the two groups used the t test. The results of the research obtained were tcount of 2,233 and t table at a significant level of 0,05 of 2,024, then tcount> ttable. Then H0is rejected and H1is accepted. Thus it was concluded that there were differences in the average learning outcomes of students taught using the Inquiry Training learning model and the Group Investigation learning model.